Answer:
(x – h)^2 + (y – k)^2 = r^2,
Step-by-step explanation:
(x - 0)^2 + (y +2)^2 = 3^2
please give me brainliest
don't fail
y = 13x + 10 is a proper equation for this word problem
Answer: 3,295.5
Step-by-step explanation:
Answer:
x = 4 + sqrt(73) or x = 4 - sqrt(73)
Step-by-step explanation by completing the square:
Solve for x:
(x - 12) (x + 4) = 9
Expand out terms of the left hand side:
x^2 - 8 x - 48 = 9
Add 48 to both sides:
x^2 - 8 x = 57
Add 16 to both sides:
x^2 - 8 x + 16 = 73
Write the left hand side as a square:
(x - 4)^2 = 73
Take the square root of both sides:
x - 4 = sqrt(73) or x - 4 = -sqrt(73)
Add 4 to both sides:
x = 4 + sqrt(73) or x - 4 = -sqrt(73)
Add 4 to both sides:
Answer: x = 4 + sqrt(73) or x = 4 - sqrt(73)
Answer:
80
Step-by-step explanation:
the 80 is the tenth part so you do nothing its a trip up qustion